Módulos funcionais de software para microcontroladores ARM - Melo, Reuber Regis de (Universidade Federal Rural do Semi-Árido, 2013)
The Microcontrollers Units (MCUs) are components used in a variety of devices, ranging from household to industrial use. In industrial automation MCUs are present in the equipment responsible for motor control, valve actuation, measurements and other functions. Currently, the MCUs based on Advanced RISC Machine (ARM) technology are highlighted due to its higher capacity performance, lower power consumption and low cost. These MCUs ARM feature software composition consist of three elements: an embedded operating system, device drivers and applications in general. Given this composition software of ARM MCUs, this paper presents a solution called Functional Modules for ARM (MoFA), with the aim of offering an alternative way in the development of automation and control. These modules are software applications that can be developed for different operating systems on embedded ARM MCUs, such as AndroidTM, embedded Linux distributions and Windows CE. The MoFA has basically four modules: module of control algorithmic for developing and execution of control routines of an automation system, the data storage module to store information needed of the process automation, communication module for remote access to ARM MCU and the analog and digital inputs and outputs module for manipulation of I/O ports of MCU. To validate the MoFA were implemented two applications: a supervisory system for photovoltaic panels and a PI control system liquid level. The results for each application are presented at the end of this work. For the development of these two applications was used the ARM Microcontroller of Tiny6410 Kit of Friendly ARM. The study was conducted at the laboratory of GEDEA of UFERSA
Keywords: Automação; Sistemas de controle; Sistemas embarcado; Microcontroladores ARM; Automation; Control systems; Embedded systems; ARM microcontrolles; ENGENHARIAS::ENGENHARIA ELETRICA